Selection Of Melon Varieties For Growing An Early Crop In The Nukus District (Texas Journal of Agriculture and Biological Sciences, 2025)
The article describes the production of small-weight export-oriented melons in the Nukus district, including the Dakaro F1 hybrid (54.1 t/ha), Londa Khandalak No. 25 (44.4 t/ha), Kolkhoznitsa (41.0 t/ha), and Kichkintoy (34.0 t/ha) in the fairy-tale cultivation of the region